Novel Porous Chitosan Resin for the Removal of Cd(II) from Aqueous Solutions - Cang, Hui; Lu, Yu; Xu, Qi (Asian Journal of Chemistry, 2013)
A novel chitosan derivative, porous tetraethylenepentamine-type chitosan resin, was chemically modified by chloromethyloxirane and tetraethylenepentamine. The uptake behaviour of resin towards Cd(II) was studied in aqueous medium, where the maximum adsorption capacity of the resin was 125.1 mg/g at pH 8.0 at room temperature. Kinetic studies referred that the uptake reaction is pseudo second order. The uptake reaction is a monolayer and found to be endothermic. Interference of other cations and anions in Cd(II) adsorption was found to be significant. The resin was regenerated effectively (desorption ratio »98 %) using a mixture of 2 M NaCl and 0.5 M and can be regenerated many times as well as stable performance in adsorption of Cd(II).